ИХТИСОСЛАШГАН МАКТАБЛАРДА БАҲОЛАШГА ОИД МАСАЛАЛАР ТУРЛАРИ ВА УЛАРНИ ЕЧИШ УСУЛЛАРИ - Сойипов, Ж.Ж. (SCIENCE and SOCIETY, 2022)
This article shows the methods of developing students’ interest in physics, the organization of independent learning in practical classes. In addition, aspects of the use of questions are shown related to the assessment of classes in the classroom and in extracurricular activities in academic lyceums and secondary schools taught through advanced physics training.